Effect of Task-Oriented Exercises With and Without Altered Sensory Input on Balance and Falls in Subjects with Parkinson’s Disease - Joshi, Anchal; Kunduru, Sudheera (RGUHS Journal of Physiotherapy, 2021)
Background Task-oriented training is a method which focuses on specific functional tasks associated with the musculoskeletal and neuromuscular systems. During task-oriented training a variety of movements are practiced to reduce compensatory movements and to increase adaptive movements. Postural instability and resulting falls are major factors determining quality of life morbidity and mortality in individuals with Parkinsonrsquos disease. So the present study aimed to determine the effect of task-oriented exercises with and without altered sensory input on balance and falls in subjects with Parkinsonrsquos disease.Objective To determine and compare the effect of task-oriented exercises with altered sensory input and task-oriented exercises without altered sensory input on balance and falls efficacy in subjects with Parkinsonrsquos disease.Method Thirty subjects between the age group of 60-75 years diagnosed with idiopathic Parkinsonrsquos disease were randomly assigned to one of the two groups Group A and Group B. They participated in a task-oriented exercise program for 1 hour in a day 3 times per week for 6 weeks focusing on balance and falls. Exercises were performed under conditions of vision and surface manipulation with altered sensory input in Group A and under normal conditions without altered sensory input in Group B. Pre-and post-assessment of balance and falls was done using Berg Balance Scale and Falls Efficacy Scale-International.Results Both the groups showed statistically significant improvement in balance and falls reduction Plt0.001. But when both the groups were compared there was an improvement of balance and falls reduction that was statistically more significant in Group A than in Group B plt0.05.Conclusion This study concluded that task oriented exercises both with or without altered sensory input were beneficial in improving balance and reducing falls. But altering the sensory input was found to be more beneficial in these subjects.